Efficacy of a Combined Acceptance and Commitment Intervention to Improve Psychological Flexibility and Associated Symptoms in Cancer Patients: Study Protocol for a Randomized Controlled Trial - García-Torres, Francisco; Gómez-Solís, Ángel; Rubio García, Sebastián; Castillo-Mayén, Rosario; González Ruíz-Ruano, Verónica; Moreno, Eliana; Moriana, Juan Antonio; Luque-Salas, Bárbara; Jaén-Moreno, María José; Cuadrado-Hidalgo, Fátima; Gálvez-Lara, Mario; Jablonski, Marcin; et al. (Frontiers in Psychology, 2022)
Psychological flexibility is a key concept of aceptation and commitment therapy. In cancer patients, it mediates with the psychological well-being and associated factors such as quality of life. Previous research have shown positive resuls of aceptation and commitment therapy in cancer patients but using mhealth tools may help to enhance these positive results in cancer settings. A three-arm randomized superiority clinical trial, with a pre-post-follow-up repeated measures intergroup design with a 1:1:1 allocation ratio is proposed. A hundred and twenty cancer patients will be randomly assigned to one of the following interventions: (1) face-to-face ACT + app (2) face-to-face ACT and (3) Waitlist control group. The primary outcome is to observe significant improvements in psychological flexibility (AAQ-II) in the face-to-face ACT + app group, after comparing baseline and post-treatment scores, and the scores will remain stables in the two assessment points, 3 and 6 months after intervention. Secondary outcomes are significant changes in anxiety and depression (HADS), quality of life (EORTC QLQ C-30), insomnia (ISI), fatigue (BFI) and post-traumatic-growth (PTGI-SF) in the same assessment points. Also, it is expected that the scores of this group will be higher than the scores of the face-to-face ACT group and the waitlist control group. This study aims to assess the efficacy of a combined intervention (face-to face ACT + app) for psychological flexibility and associated symptoms in cancer patients. The results of this protocol may help to consider the use of aceptation and commitment therapy and mhealth applications in cancer settings as a valid therapeutic choice.